The Photometric Study of EX Dra: A Dwarf Nova Exhibiting a Titled and Precessional Disk - Wei Liu; Sheng-Bang Qian; Xiang-Dong Shi; Qi-Bin Sun; Xiao-Hui Fang; Qi-Shan Wang (The Astrophysical Journal, 2024)
We present a photometric study of EX Dra, a dwarf nova that has been extensively observed by the Transiting Exoplanet Survey Satellite. The data reveal the occurrence of 20 complete outbursts, exhibiting several intriguing and rare characteristics. The light curves exhibit a distinct superorbital signal with a period of approximately P _sor ∼ 4.39(7) days, along with a negative superhump showing an approximate period of P _nsh ∼ 4.805(1) hr, indicating that the accretion disk is tilted and undergoing precession with the period of P _sor . In addition, the time-varying nature of P _sor suggests that the precession period is fluctuating.The eclipsing light minima O – C analysis during quiescence shows an oscillation with period of 3.9(5) days, which is a little shorter than the superorbital period. We contend that this is unlikely to be a sudden alteration of the orbital period, but rather, it is influenced by the tilt and precession of the accretion disk. Notably, we found an amplitude shift in the outburst behavior from 3.5 mag with a periodicity of about 26 days to an amplitude of around 2.5 mag with a periodicity of about 12 days, which persisted for 14 yr before reverting. Furthermore, we have extracted quasiperiodic oscillations in the plateau at the noneclipsed phases, characterized by periods ranging between 37 and 40 minutes.